Identification of a Novel 5′ Alternative CFTR mRNA Isoform in a Patient with Nasal Polyposis and CFTR Mutations. Issue 7 (9th April 2014) - Hinzpeter, Alexandre; de Becdelièvre, Alix; Bieth, Eric; Gameiro, Christine; Brémont, François; Martin, Natacha; Costes, Bruno; Costa, Catherine; Aissat, Abdel; Lorot, Aurélie; Prulière‐Escabasse, Virginie; Goossens, Michel; et al.
<x xml:space="preserve">Abstract</x> A novel 5' alternative CFTR transcript was identified in a 12y‐old patient presenting with isolated nasal polyposis and being heterozygous for c.2551C>T (p.Arg851*). Its characterization was made after identification of the c.‐2954G>A mutation which was shown to enhance promoter activity. The novel, presumably non‐functional, transcript could represent a novel molecular CFTR defect associated with CFTR‐related disorders. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>